Turnover intention linking compulsory citizenship behaviours to social loafing in nurses: A mediation analysis - Yildiz, Bora; Elibol, Esengul (Wiley, 2021)
Aims To propose a theoretical model of social loafing behaviours and to examine the effects of compulsory citizenship behaviours and turnover intention on nurses' social loafing behaviour. Method This cross-sectional study included 264 nurses working in public hospitals in Istanbul, Turkey. The data were gathered by using a snowball sampling method and analysed using descriptive statistical analyses, F test, t test, Pearson's correlation analysis and multiple and hierarchical linear regression analyses. Results Results indicated that compulsory citizenship behaviours were positively associated with turnover intention and social loafing. Turnover intention fully mediated the relationship between compulsory citizenship behaviours and social loafing. Conclusion Nurses who exhibit compulsory citizenship behaviours have developed turnover intentions to conserve their well-being, which led to social loafing as a resource recovery tactic. Implications for Nursing Management Training should be provided for managers and nurses to raise awareness about the possible negative effects of compulsory citizenship behaviours. To manage social loafing and turnover intention, effective and proactive solution-oriented strategies should be implemented.
Keywords: Compulsory Citizenship Behaviours; Nurses; Nursing; Social Loafing; Turnover İntention; Employee Turnover; Organizational Citizenship; Job-Satisfaction; Work; Impact; Perceptions; Commitment; Boundaries; Hospitals; Justice